Allopurinol's effect on caspase-3 and caspase-8 activity in hypoxic-ischemic newborn rats - Ozcan, Kenan; Satar, Mehmet; Canacankatan, Necmiye; Taskin, Erdal; Daglioglu, Kenan (Aves, 2013)
Aim: During reperfusion period of hypoxia-ischemia, cyclooxygenase and xanthine oxidase pathways are induced. A xanthine oxidase inhibitor, allopurinol has been shown to be neuroprotective in hypoxic-ischemic encephalopathy. Caspase-8 and caspase-3 have a key role in neuronal apoptosis. We aimed to test repeated doses of allopurinol's effect on caspase-3 and caspase-8 activities in newborn rats with hypoxic-ischemic encephalopathy. Material and Method: Seven days old newborn rats were taken and there were 10 rats in each group. After Ethical Committee was approved (TIBDAM-25), rats were subjected to left carotid artery ligation and hypoxia (8% oxygen and 92% nitrogen) for two and half hours. Hypoxic ischemic rats treated with 24 mg/kg allopurinol 30 minutes and 12 hours (AL48 group), and 30 minutes, 12 and 24 hours (AL72 group) after hypoxic-ischemic insult. Twenty four hours after last dose, rats were decapitated. The others groups were sham and saline-treated hypoxic-ischemic (H-I) group. Caspase-3 and caspase-8 activities were measured in both hemispheres. Results: There was no difference in caspase-3 and caspase-8 activities between right and left brain hemispheres in each group (p>0.05). Caspase-3 and caspase-8 activities were significantly lower in sham group when compared to H-I group, AL48 and AL72 groups (all of it, p=0.0001). Even though there were no difference activities of caspase-3 and caspase-8 between H-I group and AL48 group (p>0.05), activities of caspase-3 and caspase-8 in AL72 group were significantly lower than H-I group and AL48 group (respectively p=0.0001, p=0.001). Conclusions: Decreased activities of caspase-3 and caspase-8 in AL72 group may suggest that totally dosage of 72 mg/kg allopurinol may be effective for reducing neuronal apoptosis in newborn rats with hypoxic-ischemic insult.
Keywords: Allopurinol; caspase-3; caspase-8; hypoxic-ischemia; newborn rats